EXAMINATION OF THE ACTIVE SPORTS CONSUMPTION HABITS OF STUDENTS OF THE UNIVERSITY OF DEBRECEN - Szerdahelyi, Zoltán (Acta Carolus Robertus, 2020)
I consider the examination of the active sports consumption habits of students of the University of Debrecen to be useful in several respects. By mapping this area, measures to increase physical activity, such as the definition of facility side components, can be more effective. The Faculty of Child and Special Needs Education is in a special position compared to other faculties. Both the Hajdúböszörmény site and the sociocultural background of the students justify taking local specificities into consideration. I used a questionnaire research (N=338). In addition to socio-demographic data, the questions examined costs of leisure and leisure activities. I have analysed the extent to which students’ physical activity is affected by various socio-demographic, cultural and eco-factors. I can tell you that the income factor sits in the middle of the rankings. The income conditions are characterised by large differences between students. Students show a low inclination to invest in connection with physical activity. There was no significant link between academic achievement and the monthly costs related to sports activities. In the course of the research, I examined the types of sports activities students are willing to pay for. Hiking and exercising considered as "trendy exercising" (aerobics, zumba, spinning, jumping fitness, Nordic walking, crossfit, yoga) are high on the list. By analysing the relationship between monthly income and sports consumption, I found a significant correlation in two cases: buying season tickets for gym and "trendy exercising".